Damage detection in structures using electromechanical impedance and finite element analysis - Djemana, Mohamed; Hrairi, Meftah (Trans Tech Publications Ltd., Switzerland, 2015)
Impedance-based structural health monitoring (SHM) techniques have been developed as a promising tool for real-time structural damage assessment, and are considered as a new nondestructive evaluation method. It is gaining popularity due to its potential of reducing maintenance costs while increasing safety and reliability. This article present the results of Finite Element analysis performed for aluminum beam with bonded piezoelectric transducer (PZT). Modeled structure was excited to vibrate at high frequency range and electromechanical impedance (EMI) plots were obtained from the harmonic analysis. Notches were introduced in the beam and the damage metrics were used to assess qualitative changes in structural properties of the system. Furthermore, a parametric study of the effects of different variables was carried out. The numerical results show a good agreement was observed.